Análise da associação entre tagSNPs no gene IL1B e aspectos clínicos com pré-eclâmpsia grave - Galvão, Larissa Paes Leme (2017)
Introduction: Preeclampsia (PE) is characterized by the occurrence of gestational hypertension and proteinuria. Cytokines as IL-1 can cause an exaggerated inflammatory process causing oxidative stress and endothelial damage. In PE, and considering the ethnic variation, these cytokines are encoded through their encoding gene: among them the IL1B gene. Objectives: In order to investigate the association of polymorphisms in the IL1B gene in women with preeclampsia and the influence of possible maternal, environmental and genetic risk factors, a case-control study was conducted in two reference maternity hospitals in the state of Sergipe. Methods: An interview was done and the DNA of 456 volunteers collected for analysis. The predominance of melanoderma and feoderma individuals is emphasized here: few studies with this population are found in the literature regarding IL1B and PE. The genetic analysis aimed the representation of the gene integrally and for this purpose four tagSNPs for IL1B gene were analyzed: rs1143643, rs1143633, rs1143634 and rs1143630. The analysis of the association between the haplotypes and p values were calculated using the THESIAS software. Chi square test, Fisher test, Odds Ratio, confidence interval and multivariate logistic regression were performed. Results: Factors such as rs1143630 polimorphisms, obesity, primiparity, cesarean delivery and low level of consciousness at the time of admission to the health service were related to PE. Suggestive evidence of association between "T" allele in rs1143630 and preeclamptic women was observed. Conclusions: Clinical factors and IL1B polimorphisms were associated with severe preeclampsia. In many aspects, avoid maternal deaths related with preeclampsia is one of the most important and urgent challenges of obstetrics today.